Tag it: Issue 3/Oct 2013 Think Big, Dream Big - Universiti Malaysia Sarawak, Centre for Information Technology Development & Services (Universiti Malaysia Sarawak (UNIMAS), 2013)
In this issue of Tag-it aptly titled “Think Big, Dream Big”; we bring to the fore-front, the various ICT works that have been winning accolades both locally and internationally. All started as a thought, an idea or a dream that became reality, very much like Einstein’s body of work. Yet all are successes that put UNIMAS on the map for ground-breaking innovative ideas.